Portable, wireless, and effective internet of things-based sensors for precision agriculture - Gsangaya K.R.; Hajjaj S.S.H.; Sultan M.T.H.; Hua L.S. (Springer, 2023)
Agricultural robots; Crops; Data acquisition; Environmental technology; Internet of things; Precision agriculture; Sensor nodes; Soil moisture; Soil quality; Solar energy; Agricultural productions; Comprehensive system; Crop managements; Data-acquisition units; Environmental parameter; Environmental quality; Internet of things technologies; Operational decisions; Soil surveys; agricultural land; agricultural production; data acquisition; database; environmental quality; Internet; precision agriculture; sensor; soil management